Product allocation to cross dock and warehouse using genetic algorithm - Soleimanynanadegany, Amin (2014)
The main goal of this project is to use a genetic algorithm to allocate different product to a cross dock and warehouse of a distribution center. In spite of the enormous quantity of researches on product allocation to distribution center, allocating different products to cross dock and warehouse is less investigated. In order to fill this gap, this research was conducted analytically using a genetic algorithm to allocate different products to a distribution center. Particularly, one distribution center (located in the South East of Asia) along with 19 products were used as the case of this study. Based on the available literature, the existing constraints were evaluated and used for the aim of ranking different products based on their importance level. Finally, a genetic algorithm were used to allocate the different product to both cross dock and ware house considering the processing cost, demand, capacity and related constraints and determine the best combination of cross docking and warehouse to minimize processing cost as much as possible. The results showed that processing cost of products allocation to cross docking and warehouse can be improved through using genetic algorithm by $215 compared to Li et al.(2008).